The nationality of the foreign adoptee son of a brazilian adopter: Jurisprudential analysis - Melo , Milena Barbosa de; Cavalcanti , Rebeca (Seven Editora, 2023)
The silence of the Constitution of the Federative Republic of Brazil, of 1988, about the nationality of foreign adoptees by Brazilian parents has become the object of judicial interpretation, demanding considerations about which perception should be adopted with regard to the subject. In the first chapter, the concept of nationality and the guiding criteria for its attribution are presented – jus soli and jus sanguinis, which are discussed with emphasis. In addition, the forms of recognition of naturalization recognized by the Constitution of the Republic of 1988 are revisited and, more notably, the legal consequences that radiate from it, specifically with regard to distinctions between native Brazilians, naturalized Brazilians and between these and foreigners. A brief analysis of the requirements for the adoption of a foreign child, verifying the legislation, and the doctrinal divergence regarding the nationality of the adoptee are presented in the second chapter. The third and last chapter focuses on the current position of the Brazilian Judiciary on the recognition of the original Brazilian nationality of foreign children who are adopted by Brazilian parents. This academic essay addresses a delicate topic, little explored by academics and jurisprudence. In addition, the assertions mentioned do not dare to enter into a conclusion per se, but allow reflections in the light of the Principle of the Dignity of the Human Person, guiding the so-called “Citizen Constitution” and the fundamental principle of nationality, which establishes the legal-political bond that unites the people to the State, allowing, of course,  an incursion into other future studies. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-036